Gitelman Syndrome Presenting with Hypomagnesemia, Hypokalemia and Hypocalciuria: A Case Report - Uzunlulu, Mehmet (Medeni Med J, 2019)
Gitelman syndrome is a a rarely seen autosomal recessive renal tubulopathy characterized by inherited hypokalemic metabolic alkalosis with hypomagnesemia and hypocalciuria. The diagnosis of Gitelman syndrome is usually established during adolescence, but is also observed in childhood and even in the adulthood period. In this case report, we presented a 19-year-old male patient who was diagnosed as Gitelman Syndrome and admitted to the hospital with symptoms of muscle weakness, cramps and weakness.